The correlation between lifestyle health behaviors, coping style, and mental health during the COVID-19 pandemic among college students: Two rounds of a web-based study - Zhang, Yi; Tao, Shuman; Qu, Yang; Mou, Xingyue; Gan, Hong; Zhou, Panfeng; Zhu, Zhuoyan; Wu, Xiaoyan; Tao, Fangbiao (Frontiers in Public Health, 2023)
Background: During the last months of 2019, worldwide attention has focused on a pandemic of COVID-19, and the pandemic spread rapidly, becoming a public health emergency of international concern. Objective: This study aimed to investigate the correlation of influencing factors and mental health symptoms among Chinese college students according to two rounds of surveys during the COVID-19 pandemic. Materials and Methods: This study was divided into two stages of cross-sectional investigation. In February 2020 and May 2020. From February 4 to February 12, 2020, 11,787 college students completed the first round of online study from 16 cities and universities in 21 in China. After 3 months, using the convenience sampling method, a survey on the cognitive and psychological status of COVID-19 among college students was conducted in 21 universities in 16 regions in May 2020. The regions among the two surveys are divided into Wuhan (District 1), neighboring Hubei (District 2), first-tier cities, namely, Beijing, Shanghai and Guangzhou (District 3), and other provinces (District 4). Results: (1) In the second round of surveys, 6803 males and 9502 females had a mean age of 20.58 ± 1.81 years. The prevalence of depressive symptoms and anxiety symptoms during COVID-19 was 30.7% and 23.9%, respectively. (2) In both surveys, college students who reported having higher ST, lower PA, higher soda beverage and tea beverage intake, Chinese herbal medicine and vitamin drinking, and decreased frequency of diet also had higher depression and anxiety symptoms. The results of the conditional process model analysis support our hypothesis that lifestyle behaviors, and coping styles are both predictors of mental health, with both direct and indirect effects moderated by gender level. In logistic regression analysis, the correlation of depression and anxiety in the second rounds of the survey was higher than that in the first survey. Conclusions: Our findings demonstrated that the prevalence of anxiety and depression in the two rounds of surveys was different, and the prevalence in the second round was higher than that in the first round, as well as that in the two rounds of surveys.